The Relation Between the Expression of latent Membrane Protein-1 - Sofia Mubarika H, Soeripto, Murtono C, (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: In vitro studies reveal that LMP1 induces the expression of many factors for invasion and metastasis. Objective: The aims of this study were to investigate the role of LMP1 expression on the status of Nand M that take place either directly or sequentially through its relation with the expression IL4, IL6. IL 10. IFN-gamma. Gran2yme B and with protease MMP2. MMP9. either in the serum or in the tumour tissue. Methods: Forty one 41 EBER-RISH confirmed NPC cases with parallel serum were used for this study. Immunohistochemistry was used to study the expression of proteins in the tissue. The serum level of proteins were determined with ELISA. Statistical analysis used Lisrel 8.50. Results: No correlation between the expression of LMP1 with the status of Nand M of the tumour either directly or that sequentially took place through the expression of the cytokines and MMPs either in the tumour tissue or the serum level. The serum level of MMP9 was correlated with the serum level of IL6, the status of N. and the expression of IL 10. Status N was correlated with serum level of MMP2. Conclusion: There is a process that sequentially took place through the increase of the cytokines. MMPs, either in the tumour tissue or serum level and N. M status. LMP1 expression was not involved in the process. Key words: NPC - metastasis - MMP - cytokine